Pelatihan pemanfaatan digital marketing: solusi alternatif pengembangan UMKM Dusun Puringan Desa Sidomulyo Magelang - Azzahro, Rizki Desi; Khasanah, Muflikhatul; Awalia, Rizka Ummama; Rohman, Ahmad Nur; Setyaningsih, Wahyu (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
Micro, Small and Medium Enterprises (MSME) development is essential for local economic growth. However, MSMEs often face business licensing, production efficiency, and marketing challenges. Adaptive and innovative are the primary keys for MSMEs to continue to develop their businesses. The partner's problems are the production process, which still takes time, limited employment, and marketing, which is not yet optimal. This is because partners' knowledge regarding digital marketing strategies is still low. This service activity aims to provide adequate understanding regarding concepts and practical assistance in implementing digital marketing strategies to overcome production processes that still take time, limited employment, and marketing that is not yet optimal. The service method is carried out by training MSME owners on platforms such as social media, websites, and analytical tools to expand reach and increase sales. The results of the service after direct training activities show that MSME partners have been able to understand digital marketing concepts and implement digital marketing strategies well through social media platforms.